Russia of the tsars - Strickler, Jim, 1956- (San Diego, CA : Lucent Books, 1998)
Describes the history of Russia under the tsars, from its beginnings before 1598 to the Revolution of 1917.
Includes bibliographical references (p. 88-91) and index.
Keywords: Russia -- History -- Juvenile literature; Russia -- History